Distributed creativity: collaboration and improvisation in contemporary music - Clarke, Eric F.; Doffman, Mark (New York Oxford university press, 2017)
Creative practice in music, particularly in traditional concert culture, is commonly understood in terms of a rather stark division of labour between composer and performer. But this overlooks the distributed and interactive nature of the creative processes on which so much contemporary music depends. The incorporation of two features-improvisation and collaboration-into much contemporary music suggests that the received view of the relationship between composition and performance requires reassessment. Improvisation and collaborative working practices blur the composition/performance divide and, in doing so, provide important new perspectives on the forms of distributed creativity that play a central part in much contemporary music.Distributed Creativity: Collaboration and Improvisation in Contemporary Music explores the different ways in which collaboration and improvisation enable and constrain creative processes. Thirteen chapters and twelve shorter Interventions offer a range of perspectives on distributed creativity in music, on composer/performer collaborations and on contemporary improvisation practices. The chapters provide substantial discussions of a variety of conceptual frameworks and particular projects, while the Interventions present more informal contributions from a variety of practitioners (performers, composers, improvisers), giving insights into the pleasures and perils of working creatively in collaborative and improvised ways.